Development and Evaluation of Nanoformulation for Targeted Delivery of Gemcitabine for the treatment of Lung Cancer - Kumar, Krishan (IIT(BHU) Varanasi, 2023)
Abstract is available in the attachment.
Keywords: Pharmaceutical Engineering